The Scope of competence of the administrative judiciary in the pension dispute (A comparative study) - Kamel Abdullah Abu Hasna Al-Ajajibi , Researcher. Ali; Naeem Khudhair Al-Khafaji , Assist. Prof. Dr. Salim (Basra studies journal, 2023)
In this research, we examine the role played by the administrative judiciary in settling disputes arising from the application of retirement laws and regulations, specifying its jurisdiction. After investigating the issue around which the research revolves, it became evident that the method currently employed to resolve these disputes in Iraq is not sufficient to strike a balance between conflicting interests. These interests involve the administrative authority's right to issue administrative decisions and the retirees' interest in protecting their retirement rights. The Iraqi legislator has adopted an approach in handling these disputes that differs from its approach in other disputes. It established a specialized administrative committee entrusted with the task of resolving disputes arising from the application of retirement laws. The committee's jurisdiction is specifically focused on settling retirement-related disputes.